Green Revolution in Sub-Saharan Africa: Implications of Imposed Innovation for the Wellbeing of Rural Smallholders. (February 2016) - Dawson, Neil; Martin, Adrian; Sikor, Thomas
Highlights: Critical analysis of modern "Green Revolution" agricultural policies in Rwanda. Mixed methods study to assess wellbeing and policy impacts on rural households. Policy framing, governance, and deficient assessment overlook considerable impacts. Imposed changes impede subsistence, diminish tenure, and exacerbate inequality. Mitigation/adaptation recommended to support pro-poor tenure and cultural practice. Summary: Green Revolution policies are again being pursued to drive agricultural growth and reduce poverty in Sub-Saharan Africa. However conditions have changed since the well-documented successes of the 1960s and 1970s benefitted smallholders in southern Asia and beyond. We argue that under contemporary constraints the mechanisms for achieving improvements in the lives of smallholder farmers through such policies are unclear and that both policy rationale and means of governing agricultural innovation are crucial for pro-poor impacts. To critically analyze Rwanda's Green Revolution policies and impacts from a local perspective, a mixed methods, multidimensional wellbeing approach is applied in rural areas in mountainous western Rwanda. Here Malthusian policy framing has been used to justify imposed rather than "induced innovation". The policies involve a substantial transformation for rural farmers from a traditional polyculture system supporting subsistence and local trade to the adoption of modern seed varieties, inputs, and credit in order to specialize in marketable crops and achieve increased production and income. Although policies have been deemed successful in raising yields and conventionally measured poverty rates have fallen over the same period, such trends were found to be quite incongruous with local experiences. Disaggregated results reveal that only a relatively wealthy minority were able to adhere to the enforced modernization and policies appear to be exacerbating landlessness and inequality for poorer rural inhabitants. Negative impacts were evident for the majority of households as subsistence practices were disrupted, poverty exacerbated, local systems of knowledge, trade, and labor were impaired, and land tenure security and autonomy were curtailed. In order to mitigate the effects we recommend that inventive pro-poor forms of tenure and cooperation (none of which preclude improvements to input availability, market linkages, and infrastructure) may provide positive outcomes for rural people, and importantly in Rwanda, for those who have become landless in recent years. We conclude that policies promoting a Green Revolution in Sub-Saharan Africa should not all be considered to be pro-poor or even to be of a similar type, but rather should be the subject of rigorous impact assessment. Such assessment should be based not only on consistent, objective indicators but pay attention to localized impacts on land tenure, agricultural practices, and the wellbeing of socially differentiated people.